Estudio económico para la creación de una panadería y pastelería en el sector Bastión Popular Bloque # 2 – Norte de Guayaquil - Chuquiana Tubón, Alex Dario (2024)
This degree project entitled the economic study for the creation of a bakery and pastry shop in the sector Bastión Popular Block # 2 - North of Guayaquil, focuses on evaluating the possibility of establishing a bakery and pastry shop in Bastión Popular, Guayaquil, Ecuador. As a country with an economic base centered on agriculture, Ecuador presents significant opportunities in the food sector, specifically Bastión Popular emerges as an enclave with potential for business initiatives related to bakery and pastry. The economic assessment will address various aspects, such as local market demand, existing competition, operating costs, and revenue projections. Aspects such as strategic location, consumer preferences, and market trends will be taken into account to determine the long-term viability of the proposed bakery and pastry shop. Additionally, the socioeconomic implications of this project will be explored, analyzing its influence on employment generation and local development. The importance of providing high quality products will be highlighted, as well as the option of introducing innovative elements to stand out in the market. Finally, recommendations supported by the findings of the economic analysis will be presented, with the purpose of supporting informed decision making for the successful creation of the bakery and pastry shop in Bastion Popular, Guayaquil.